Strategi Komunikasi Pemerintah dalam Mensosialisasikan Aplikasi SiKesal untuk Mendukung Program Smart City di Jambi - Nella Ervina; Dessy Andamisari (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2026)
The SiKesal application serves as one of the means to involve citizens in the development of Jambi City. Success in implementing this information technology innovation is reflected in users’ willingness to accept and use it, closely related to the ease and benefits obtained. This study aims to analyze and elaborate the government communication strategy applied to disseminate the SiKesal application in supporting the Smart City program in Jambi. Descriptive‑qualitative method with case‑study approach is used. Data were gathered through direct observation and in‑depth interviews covering seven informant groups: mayor or deputy mayor, head of Communication and Information Agency, active users, non‑users, community leaders, academic observers, and mass media representatives. Analysis follows four stages: situation analysis, goal and strategy formulation, implementation, and evaluation. Results show that the strategy is built upon thorough understanding of barriers in public service, especially regarding accessibility and efficiency in submitting complaints. Strategic objectives focus on improving service quality through digital innovation so citizens can report issues instantly anytime and anywhere without visiting government offices physically. This mechanism facilitates access to public services and ensures faster responses from relevant agencies to support the Smart City initiative effectively.